Trophic ecology and nutritional status of northern shrimp in Canada’s sub-Arctic - Gustavo Yunda-Guarin; Sheila Atchison; Krista D. Baker; Frédéric Cyr; Christopher C. Parrish; Wojciech Walkusz; Jonathan A. D. Fisher; Tyler D. Eddy (PLoS ONE, 2025)
In the Northwest Atlantic Ocean, northern shrimp (Pandalus borealis) play key ecological roles as mid-trophic level consumers and as prey to higher-trophic level predators, including commercial fish species. However, the effects of changing environmental conditions and biological processes on trophic interactions in sub-Arctic ecosystems, particularly on lipid storage and nutrient transfer from intermediate to high trophic levels, remain unclear. Biochemical tracer methods (i.e., fatty acids and stable isotopes) were employed to study the trophic ecology and stage-specific nutritional condition of P. borealis across different spatial and seasonal scales. Trophic markers indicated significant contributions from both diatoms and zooplankton to the diet of P. borealis and highlighted the adaptability of this species to opportunistic feeding strategies based on sinking phytodetritus. Our results revealed a strong seasonality in the lipid composition of P. borealis, with lipid dynamics being highly influenced by environmental conditions and resource availability. The primary lipid classes in P. borealis were storage triacylglycerols, accounting for over 50% of lipids observed, followed by membrane phospholipids. Eggs from ovigerous females exhibited the highest concentrations of total lipids and essential fatty acids, such as omega-3 fatty acids, underscoring the important ecological role of eggs in sub-Arctic food webs by providing high-quality lipid sources. Additionally, our findings indicated an increase in the total lipid content of shrimp eggs from spring to summer, suggesting that the early stages of P. borealis are vulnerable to changes in the timing of seasonal primary production, when females store large reserves of energy-rich lipids. This study highlights the large seasonal and temporal variability in the nutritional status of P. borealis and underlines the importance of understanding lipid dynamics in assessing the resilience of populations to environmental changes.